(untitled) (Baghdad Science Journal, 2025)
The embryonic development of the Mosquito fish(Gambusia affinis) eye lens was investigated using light microscopy .The results indicated that the embryonic development of the lens does not correspond to that of the non spherical lenses of terrestrial vertebrates .This study showed that a very small cavity in the lens vesicle appears during development ,but it differs from that of the mammalian lens. The most important aspect in this study is that ,the posterior edge of the simple cuboidal epithelium which covers the anterior half of the surface of the lens is situated well beyond the equatorial region of the lens .As a result , the germinal and transitional zones became closer to the posterior pole rather than the anterior pole of the lens. This might be an important factor in causing the lens to be spherical rather than being biconvex.